Phylogeny and biogeography of bees of the tribe Osmiini (Hymenoptera: Megachilidae) - Praz, Christophe J.; Müller, Andreas; Danforth, Bryan N.; Griswold, Terry, L.; Widmer, Alex; Dorn, Silvia (My University, 2008)
The Osmiini (Megachilidae) constitute a taxonomically and biologically diverse tribe of bees. To resolve their generic and suprageneric relationships, we inferred a phylogeny based on three nuclear genes (Elongation factor 1-α, LW-rhodopsin and CAD) applying both parsimony and Bayesian methods. Our phylogeny, which includes 95 osmiine species representing 18 of the 19 currently recognized genera, is well resolved with high support for most basal nodes. The core osmiine genera were found to form a well-supported monophyletic group, but four small genera, Noteriades, Afroheriades, Pseudoheriades and possibly Ochreriades, formerly included in the Osmiini, do not appear to belong within this tribe. Our phylogeny results in the following taxonomic changes: Stenosmia and Hoplosmia are reduced to subgeneric rank in Hoplitis and Osmia, respectively, Micreriades is recognized as a subgenus in Hoplitis and the subgenus Nasutosmia is transferred from Hoplitis to Osmia. We inferred a biogeographic scenario for the Osmiini applying maximum likelihood inference and models of character evolution. We provide evidence that the Osmiini originated in the Palearctic, and that extensive exchanges occurred between the Palearctic and the Nearctic. The latter finding may relate to the fact that many osmiine species nest in wood or in stems, facilitating dispersal by overseas transport of the nests.
Keywords: Biogeography; Bayesian analysis; Maximum likelihood; Ancestral; Character evolution; Nesting behavior